Democracy, development and decentralisation in India : continuing debates - Sengupta, Chandan; Corbridge, Stuart (New Delhi ; Abingdon : Routledge, 2010)
Contributed articles.
Based on presentations at a workshop organized by the Development Studies Institute, LSE and the Centre for Development Studies, TISD in London, June 2007.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Democracy -- India -- Congresses; Decentralization in government -- India -- Congresses; India -- Economic policy -- Congresses; Electronic books